IMPROVEMENT MATHEMATICS PROBLEM SOLVING ABILITY OF THE STUDENTS TAUGHT BY USING TEAM ASSISTED INDIVIDUALIZATION COOPERATIVE LEARNING MODEL - Hasbi, M; Putri, Febriyani (Universitas Negeri Makassar, 2018)
This research was aimed at revealing the effect of using Team Assisted Individualization cooperative learning model on improvement mathematics problem solving ability in class VIII of MTsN Kota Padang. This was a Quasi Experimental research which used quantitative and descriptive approach. The population of the research was the students in class VIII of MTsN Kota Padang. By using Random Sampling technique, class VIII3 of MTsN Lubuk Buaya Kota Padang was chosen as the experimental class and class VIII7 of MTsN Koto Tangah Kota Padang was chosen as the control class. In collecting the data, observation sheet, pre-test, questionnaire and pretest-posttest were used. Based on the result of the research, some conclusions were drawn. First, mathematics problem solving ability fluctuated. Second, mathematics problem solving ability of the students taught by using Team Assisted Individualization cooperative learning model was higher than that of students taught by using conventional model. Third, mathematics problem solving of the students having high and low previous ability taught by using Team Assisted Individualization cooperative learning model was higher than that of students having high and low previous ability taught by using conventional model